Lung cancer with loss of BRG1/BRM, shows epithelial mesenchymal transition phenotype and distinct histologic and genetic features. Issue 2 (4th January 2013) - Matsubara, Daisuke; Kishaba, Yuka; Ishikawa, Shumpei; Sakatani, Takashi; Oguni, Sachiko; Tamura, Tomoko; Hoshino, Hiroko; Sugiyama, Yukihiko; Endo, Shunsuke; Murakami, Yoshinori; Aburatani, Hiroyuki; Fukayama, Masashi; et al.
<x xml:space="preserve">Abstract</x> BRG1 and BRM, two core catalytic subunits in SWI/SNF chromatin remodeling complexes, have been suggested as tumor suppressors, yet their roles in carcinogenesis are unclear. Here, we present evidence that loss of BRG1 and BRM is involved in the progression of lung adenocarcinomas. Analysis of 15 lung cancer cell lines indicated that BRG1 mutations correlated with loss of BRG1 expression and that loss of BRG1 and BRM expression was frequent in E‐cadherin‐low and vimentin‐high cell lines. Immunohistochemical analysis of 93 primary lung adenocarcinomas showed loss of BRG1 and BRM in 11 (12%) and 16 (17%) cases, respectively. Loss of expression of BRG1 and BRM was frequent in solid predominant adenocarcinomas and tumors with low thyroid transcription factor‐1 (TTF‐1, master regulator of lung) and low cytokeratin7 and E‐cadherin (two markers for bronchial epithelial differentiation). Loss of BRG1 was correlated with the absence of lepidic growth patterns and was mutually exclusive of epidermal growth factor receptor (EGFR) mutations. In contrast, loss of BRM was found concomitant with lepidic growth patterns and EGFR mutations. Finally, we analyzed the publicly available dataset of 442 cases and found that loss of BRG1 and BRM was frequent in E‐cadherin‐low, TTF‐1‐low, and vimentin‐high cases and correlated with poor prognosis. We conclude that loss of either or both BRG1 and BRM is involved in the progression of lung adenocarcinoma into solid predominant tumors with features of epithelial mesenchymal transition and loss of the bronchial epithelial phenotype. BRG1 loss was specifically involved in the progression of EGFR wild‐type, but not EGFR‐mutant tumors.